2016
DOI: 10.1093/mnras/stw920
|View full text |Cite
|
Sign up to set email alerts
|

Radio synchrotron emission from secondary electrons in interaction-powered supernovae

Abstract: Several supernovae (SNe) with an unusually dense circumstellar medium (CSM) have been recently observed at radio frequencies. Their radio emission is powered by relativistic electrons that can be either accelerated at the SN shock (primaries) or injected as a by-product (secondaries) of inelastic proton-proton collisions. We investigate the radio signatures from secondary electrons, by detailing a semi-analytical model to calculate the temporal evolution of the distributions of protons, primary and secondary e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(90 citation statements)
references
References 123 publications
2
88
0
Order By: Relevance
“…(a) We numerically calculated broadband spectra of CR-induced non-thermal emission from interacting SNe, taking into account various processes such as electromagnetic cascades in the post-shock CSM as well as the attenuation in the pre-shock CSM. The electromagnetic cascade is unavoidable, although its detailed effect was not included in the previous literature (Murase et al 2011;Zirakashvili & Ptuskin 2016;Petropoulou et al 2016). We found that GeV gamma-ray spectra are insensitive to s p thanks to the cascade, and the attenuation effect can reduce the flux only modestly, which ensures that gamma rays can be used as a probe of shock interactions in dense environments that are difficult to directly observe in visible light, X rays, and radio waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) We numerically calculated broadband spectra of CR-induced non-thermal emission from interacting SNe, taking into account various processes such as electromagnetic cascades in the post-shock CSM as well as the attenuation in the pre-shock CSM. The electromagnetic cascade is unavoidable, although its detailed effect was not included in the previous literature (Murase et al 2011;Zirakashvili & Ptuskin 2016;Petropoulou et al 2016). We found that GeV gamma-ray spectra are insensitive to s p thanks to the cascade, and the attenuation effect can reduce the flux only modestly, which ensures that gamma rays can be used as a probe of shock interactions in dense environments that are difficult to directly observe in visible light, X rays, and radio waves.…”
Section: Discussionmentioning
confidence: 99%
“…The escape fraction is phenomenologically introduced to represent effects of various low-energy photon absorption processes (Murase et al 2014). Follow-up observations at high-frequency radio bands are important (Murase et al 2014;Petropoulou et al 2016), and the hadronic scenario predicts…”
Section: Introductionmentioning
confidence: 99%
“…The production rates of accelerated protons and neutrinos (at a fixed energy) are expected to decrease beyond the deceleration radius, since they scale, respectively, as v 3 sh and v 2 sh (e.g. Petropoulou et al 2016). Furthermore, the neutrino production rate is expected to decrease significantly beyond r w , where the density of the medium is much lower than n(r w ).…”
Section: Model and Methodsmentioning
confidence: 99%
“…Mastichiadis 1996;Kirk et al 1998). Neutrinos are produced at a rate dictated by the relativistic proton distribution and the non-relativistic proton density of the shocked CSM, which is assumed to be uniform and equal to 4n(r) (for details, see Petropoulou et al 2016), and they escape from the shell without any losses. The equations for the proton and neutrino distributions may be written as:…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation